PEMBUATAN BRIKET ARANG DARI CAMPURAN CANGKANG BINTARO DAN TEMPURUNG KELAPA MENGGUNAKAN PEREKAT AMILUM - Febriana, Ida; ., Sofia; Zubaidah, Nyayu; Kurniawan, Ade (KINETIKA, 2015)
Charcoal briquette is a smokeless fuel which is a type of solid fuel substances made flying low enough so that the smoke generated in the utilization of health care will not interfere with the user's own briquettes. In this study, charcoal briquettes made from bintaro waste fruit and betung bamboo using amylum adhesives. This study aims to obtain briquettes bioarang with the best quality by varying the carbonization temperature and composition of raw materials. The method used in this study is experiments or experimental methods. Variation of carbonization temperature used was 350 0C, 400 0C and 450 0C, with a ratio of raw material composition of bintaro fruit and betung bamboo 50%: 50%, 40%: 60%, and 30%: 70%. This briquette-making through several stages of the preparation of raw materials, the initial analysis, the making of briquette and final analysis. The results from this study that the composition of raw materials bintaro fruit and betung bamboo carbonization temperature of 400 C with Inherent Moisture valuesobtained for 2.13%, 2:66% ash, volatile matter content of 25.33%, 72% fixed carbon and calorific value 6775.6 cal / g. The authors conclude that the composition of the raw material of bintaro fruit and betung bamboo 50%: 50% obtained an optimum charcoal briquettes. In this case I suggest to do some research of fruit bintaro and coal in order to obtain a higher calorific value, so that the resulting charcoal briquettes have the best quality.